Photoemission spectra of indium selenide - Katerynchuk, V.M.; Kovalyuk, M.Z.; Tovarnitskii, M.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
For layered InSe crystals photoluminescence spectra were investigated and the corresponding radiative transitions were analyzed. It was found that along with the band-to-band transitions the radiative ones with participation of impurity levels plays a substantial role in the light emission spectrum of the semiconductor. This fact is confirmed by the intensities of the radiative bands for the impurity level – c(v)-band transitions and the donor-acceptor recombination. The temperature dependences of the spectrum in the range of 100 to 300 К have also enabled to ascertain the dynamics of these radiative transitions. At the temperatures 180 to 300 К, the bands associated with the indirect transitions involving indirect free excitons are more intensive. At 100…180 К, the intensity of the bands corresponding to the direct transitions with participation of direct free excitons increases. We have determined the energies of the observed photoluminescence bands, and the band diagram of the corresponding radiative transitions in InSe has been built.